Interindividual differences contribute to variation in microbiota composition more than hormonal status: A prospective study - Jackova, Zuzana; Stepan, Jan J.; Coufal, Stepan; Kostovcik, Martin; Galanova, Natalie; Reiss, Zuzana; Pavelka, Karel; Wenchich, Laszlo; Hruskova, Hana; Kverka, Miloslav (Frontiers in Endocrinology, 2023)
Aims: Ovarian hormone deficiency is one of the main risk factors for osteoporosis and bone fractures in women and these risks can be mitigated by menopausal hormone therapy. Recent evidence suggests that gut microbiota may link changes in estrogen levels and bone metabolism. The aim of this study was to analyze specific shifts in gut microbiota related to ovarian hormones changes induced by oophorectomy and subsequent hormonal therapy in women. The aim of this study was to investigate the potential relationship between hormonal and bone changes induced by oophorectomy and subsequent hormonal therapy and shifts in gut microbiota composition. Methods: We collected 159 stool and blood samples in several intervals from 58 women, who underwent bilateral oophorectomy. Changes in fecal microbiota were assessed in paired samples collected from each woman before and after oophorectomy or start of hormone therapy. Bacterial composition was determined by sequencing the 16S rRNA gene on Illumina MiSeq. Blood levels of estradiol, FSH, biomarkers of bone metabolism, and indices of low-grade inflammation were measured using laboratory analytical systems and commercial ELISA. Areal bone mineral density (BMD) at lumbar spine, proximal femur and femur neck was measured using dual-energy X-ray absorptiometry. Results: We found no significant changes in gut microbiota composition 6 months after oophorectomy, despite major changes in hormone levels, BMD, and bone metabolism. A small decrease in bacterial diversity was apparent 18 months after surgery in taxonomy-aware metrics. Hormonal therapy after oophorectomy prevented bone loss, but only marginally affected gut microbiota. There were no significant differences in β-diversity related to hormonal status, although several microbes (e.g. Lactococcus lactis) followed estrogen levels. Body mass index (BMI) was the most significantly associated with microbiota variance. Microbiota was not a suitable predictive factor for the state of bone metabolism. Conclusions: We conclude that neither loss of estrogens due to the oophorectomy nor their gain due to subsequent hormonal therapy is associated with a specific gut microbiota signature. Sources of variability in microbiota composition are more related to inter-individual differences than hormonal status.